Flash Chromatography Application for Risperidone Purification - G. S. Trush; I. Y. Halkevych (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Relevance. Biological samples for forensic-chemical investigation are complicated multi-component systems.